Examining HIV/AIDS-Related Stigma at Play: Power, Structure, and Implications for HIV Interventions. Issue 12 (14th October 2020) - Khan, Shamshad
ABSTRACT: Drawing on critical theoretical perspectives and ethnographic field research related to HIV/AIDS in northern India, this paper argues for a cultured-centered approach to stigma reduction interventions and communication practices that are based on an assessment of larger social and structural processes on the one hand and the lived experiences and narratives of people living with HIV (PLWH) on the other. This paper suggests that while the complex nature of stigma, particularly as it relates to HIV/AIDS, makes it difficult to understand and respond to, this problem is further exacerbated by a largely individual and behavior-centered research that still dominates the field of Health Communication. Such research sees human cognition as the main source of stigma and underplays issues of power, structure, domination, and control. More specifically, and with concrete examples from the everyday lived experiences of PLWH – such as their experiences within family and health-care settings, this paper demonstrates how power and structure deeply impact their lives and remain central to their experience of (and resistance to) stigma, thus opening up space for alternative theorizing and practices in Health Communication.